Graphene oxide mimics biological signaling cue to rescue starving bacteria - Jackman, Joshua A. (2022)
There is extensive debate about how 2D nanomaterials such as graphene oxide (GO) affect bacteria. Various effects of GO are proposed, including bacterial growth inhibition or enhancement, killing, and no activity. Herein, we report that GO protects Staphylococcus aureus bacterial cells from death in starvation conditions with up to a 1000-fold improvement in cell viability. Transcriptomic profiling reveals that bacterial cells in starvation conditions generally shut down metabolic activity, while only cells incubated with GO increase production of specific enzymes involved in the glyoxalase detoxification pathway along with repressed autolysis. The oxygen-containing functional groups of GO resemble the molecular structure of methylglyoxal, which bacteria produce to adapt to nutrient imbalances and is detoxified by glyoxalase enzymes. The ability of GO to enable bacterial cell survival in starvation conditions and accompanying cellular responses support that bacterial cells perceive GO as a methylglyoxal-mimicking nanomaterial cue to reshuffle cellular metabolism and defenses.